2013
DOI: 10.1007/s11255-013-0521-0
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant peritoneal dialysis relative to hemodialysis improves long-term survival of kidney transplant patients: a single-center observational study

Abstract: Pretransplantation dialysis modality is associated with long-term patient survival, with outcomes favoring peritoneal dialysis over hemodialysis. However, the pretransplant dialysis modality does not influence long-term graft loss risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
16
0
1
Order By: Relevance
“…We had no significant differences in the incidence of AR, which is in line with recent studies [ 3 , 6 , 11 , 12 ]. This may be due to the availability of and rational novel immunosuppressive protocols nowadays.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We had no significant differences in the incidence of AR, which is in line with recent studies [ 3 , 6 , 11 , 12 ]. This may be due to the availability of and rational novel immunosuppressive protocols nowadays.…”
Section: Discussionsupporting
confidence: 92%
“…Our results indicated both the immediate and long-term renal function, the serum creatinine and urine output, were similar between the HD and PD, consistent with other studies [ 6 , 11 ]. In our study, the baseline serum creatinine was higher in PD than HD patients.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, as suggested by experimental studies, we found that preserved daily urinary volume rather than type of dialysis itself was a risk factor for primary nonfunction. In fact, a recent single‐center study suggests that the pretransplant dialysis modality does not influence long‐term graft loss risk . However, large observational studies indicate that peritoneal dialysis patients may experience increased rates of graft thrombosis and early graft failure .…”
Section: Discussionmentioning
confidence: 99%